ANALISIS DETERMINAN TINGKAT KEMISKINAN DI KABUPATEN SUMBAWA: TINGKAT PENGANGGURAN TERBUKA, UPAH MINIMUM DAN PDRB - Purwadinata, Subhan; Tara, Ulan (Pusat Riset dan Publikasi, 2024)
This study aims to analyze the determinants of poverty rate in Sumbawa District, which in this study was thought to be influenced by the open unemployment rates, minimum wages and GRDP, either partially or simultaneously. The type of this study was associative. The type of data used was quantitative obtained from secondary sources through annual reports, documents and archives collected and published by the Central Statistics Agency (BPS) of Sumbawa District regarding the open unemployment rate, minimum wage, GRDP and poverty level in Sumbawa Regency in 2010-2021. Data analysis was carried out using multiple linear regression analysis, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and determinant coefficient testing (R2). The results of this study showed that in partially the open unemployment rate had a positive and significant effect on the poverty rate in Sumbawa District, and GRDP had a negative and significant effect on the poverty rate in Sumbawa District, but the minimum wage had no significant effect on the poverty rate in Sumbawa District. Meanwhile in simultaneously, the open unemployment rate, minimum wage and GRDP had a significant effect on the poverty rate in Sumbawa District. The ability of the open unemployment rate, minimum wage and GRDP variables to influenced the poverty rate in Sumbawa District was 94.8%, while the remaining of 5.2% was influenced by other variables outside this study model, such as education and health factors, economic growth and human development index.